2021
DOI: 10.1108/pr-03-2021-0170
|View full text |Cite
|
Sign up to set email alerts
|

The university-to-work transition: responses of universities and organizations to the COVID-19 pandemic

Abstract: PurposeThe purpose of this study is to understand how universities and organizations have responded to the impact of the COVID-19 pandemic in terms of preparing university students and recent graduates to enter the global labor market, using the accounting, banking and finance sector as a case study. The two research questions are (1) How can university career services and organizations work individually and collaboratively to best develop early career talent following the COVID-19 pandemic? (2) What are the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 40 publications
(81 reference statements)
3
65
0
Order By: Relevance
“…Our findings suggest that university careers services need to provide more significant support to students and recent graduates. The results align with those of Donald et al [ 56 ], who reported that career counsellors at universities have been experiencing unprecedented demands for services from students and recent graduates since the COVID-19 pandemic. However, the same study found that university careers services often lacked the resources to provide the level of support that students required, suggesting the need for additional investment.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings suggest that university careers services need to provide more significant support to students and recent graduates. The results align with those of Donald et al [ 56 ], who reported that career counsellors at universities have been experiencing unprecedented demands for services from students and recent graduates since the COVID-19 pandemic. However, the same study found that university careers services often lacked the resources to provide the level of support that students required, suggesting the need for additional investment.…”
Section: Discussionsupporting
confidence: 90%
“…This approach could be adopted in other states or regions or within different countries to solve specific problems within a localised context. This echoes the calls of Donald et al (2021) for organisations and educational institutions to foster greater levels of collaboration to prepare students for the future demands of the workplace.…”
Section: Discussionmentioning
confidence: 92%
“…However, students also highlight the ineffectiveness of some provisions due to a lack of sufficient engagement or specific, personalized advice, thereby requiring universities to develop appropriate ways of overcoming these issues. Donald et al ( 2021 ) confirmed the role of the university in the task of preparing students to embark on the university-to-work transition in the context of a competitive labour market, especially in uncertain times such as those associated with the COVID-19 pandemic. Based on this discussion, we propose the following hypothesis: H1: Career development learning positively affects students’ perceived employability.…”
Section: Literature Reviewmentioning
confidence: 99%